Improving Syllable Stress Accuracy in EFL Pronunciation: An Experimental Study Using ELSA Speak Application - Apriyawanto, Apriyawanto; Chandra, Ade; Rauf, Wahyuddin; Mulyarti, Mulyarti (Universitas Muhammadiyah Barru, 2025)
The development of technology has enabled language teachers to improve their learning objectives, media and systems. This study aimed to explore the effectiveness of the ELSA Speak Application to enhance EFL students’ pronunciation fluency and students' perspectives towards the use of the ELSA Speak App as mobile-assisted language learning at SMKS Kesehatan Babussalam Boddie, Pangkep. The research involved eight tenth-grade students in one experimental group. It employed pretests, a posttest, and a questionnaire for data collection. Both descriptive and inferential statistics methods were used to analyze the data. The analysis using Descriptive Statistics and the Paired Samples t-test revealed a significant improvement in students' pronunciation proficiency after the treatment. The mean score difference of -36.25 indicated a substantial increase in post-treatment scores, with a p-value of 0.000 confirming the results were statistically significant. The confidence interval of -39.96 to -32.54 further supports the effectiveness of the intervention. The study provided several recommendations for both teachers and learners to integrate mobile applications in the language classroom, especially ELSA Speak to improve English speaking skills in terms of pronunciation in the EFL context.